Recent advances in optical biosensing approaches for biomarkers detection - Akgönüllü, Semra; Denizli, Adil (Biosensors and bioelectronics. X, 2022)
A biomarker is an indicator for sensing the human state of health. There has been a wide-scale investigation into using portable analytical platforms for real-time monitoring of biomarkers. Biomolecular recognition, manufacturing simplification technologies, the integration of microfluidics and optics, and developed approaches to biosensor device integration have quickly moved optical-based sensors to the point of use in the laboratory. Biosensors are analytical tools incorporating a biorecognition element. Optical sensing technology is essential in modern biomedical applications as they provide quick and powerful ways to detect and distinguish target analytes from a diversity of samples. Optical-based biosensors have extra advantages such as high sensitivity, reliability, robustness, and potential to be combined on a sole chip. Recently, optical-based biosensors have been extensively investigated for the detection of diversified biomarkers using a label-free mode or by monitoring the binding of the recognition material and molecules of concern. This critical review article focuses on current progress in sensing techniques including surface plasmon resonance (SPR) surface-enhanced Raman scattering (SERS), surface-enhanced fluorescence (SEF), whispering gallery mode (WGM), photonic crystals (PCs) and opals using plasmonic nanoparticles to enhance sensitivity for detection of significant biomarkers. As a result, we overview the latest advancement in the growing use of optical biosensors for the virus, bacteria, protein, cell, and cancer biomarker detection. The requirement and future perspective of optical biosensors are also addressed. •Optical biosensors are rapid, real-time, and portable devices.•High-sensitivity optical-based biosensors provide analysis of biomarkers at low detection limits.•Optical biosensors offer a high-throughput and useful platform for the early and sensitive detection of biomarkers.•Surface modification techniques and approaches are a very important step in the design of biosensors.